Recruiting and selection their practices in banks operating in Lebanon. (c1988) - El Hajj, Nada Jamil (1988)
The success of any organization depends largely on those called to carry out its operations and to achieve its goals ,employees. Employees are then the most valuable assets in any organization ,especially in labor intensive and service businesses such as Banks. Therefore, acquiring this new "Human Asset " should receive the same importance or even more importance than acquiring a new fixed asset. The main purpose of this research is to assess the adequacy of recruiting and selection processes followed by banks operating in Lebanon. In addition , this research aims at studying the impact of recruiting an selection on employee satisfaction and turnover. Based on the results obtained, it was found that the recruiting process is adequate but it needs some improvements . while it was found that the selection process in most of the banks contacted is below standard. It was also found that employee satisfaction and turnover are dependent on the adequacy of placement and recruiting policies. Therefore, to secure the placement of the right person in the right place, to increase employee satisfaction, and to reduce employee turnover among new hires, it is recommended that the personnel managers should be personnel oriented, they should always update their knowledge through seminars and readings in personnel materials , they should assess the effectiveness of their recruiting and selection processes continuously to correct any mistakes in them, they should treat all recruits at all positions equally. Finally, they are recommended to try the use of recruitment software applications that facilitate their work and save a lot of their time.